BIMBINGAN MASYARAKAT TENTANG HARTA DAN KEPEMILIKAN DALAM PERSPEKTIF HUKUM EKONOMI SYARIAH - Fetri Fatorina; A. A Mukhtarzain; Mukhlisin Mukhlisin; Chamid Sutikno (Department of Public Administration, University Wijaykusuma Purwokerto, 2023)
Islamic insight for all Muslims is a need that must be met by each individual in order to achieve happiness in the world and in the hereafter. One of the insights that Muslims need to know is the insight into property and ownership. Ignorance and misunderstanding make someone put things out of place. One of them is the problem faced in the ta'lim an-Nissa Bobotsari assembly where some of the members have a glamorous appearance in every study and this causes social jealousy among fellow members. The purpose of this service is to direct members of the assembly to be able to dress appropriately. The methods used in this service are observation, interviews, and documentation. The result of this dedication is that after receiving the devotion material they slowly change their appearance and are able to place themselves in every study that takes place.